The Zariski Topology on the Prime Spectrum of a Module over Noncommutative Rings - (:unkn) unknown (WORLD SCIENTIFIC PUBL CO PTE LTD, 2009)
Let R be an associative ring with identity and M an R-module. Let Spec(M) be the set of all prime submodules of M. We topologize Spec(M) with the Zariski topology and prove some useful results.
Keywords: prime submodules; Zariski topology